A Reconstructive Study on How Montage Thinking Reshapes the Narrativity of Graphic Design (Journal of humanities and social sciences exploratio, 2025)
This paper focuses on studying the integration of static media and dynamic imagery as the core creation, contrasting 'expressive montage' with narrative models to solve the dilemma of temporal and spatial disjunction in visual communication. By deconstructing the Soviet montage school during the Soviet era (Eisenstein, Vertov) and the jump cut techniques of the French New Wave as theoretical foundations, a 'planarity two-axis system' is established, which can be simplified to describe the X-axis information density/Y-axis symbol abstraction. Graphic contrast triggers the perception of temporal and spatial coherence - the theory can be applied to transformability and practical feasibility. Using the 'Love Confession' series as an empirical carrier for research, I will design a cultural conflict model: (Formula: |S1-S2| X A, where S represents the symbol's cultural weight and A represents the juxtaposed area ratio), data can intuitively reflect the narrative tension of its contrasting impact. Eye movement tension experiments (sample size N=120) reveal the viewers' perception rates of image and spatial transitions.
Keywords: Editing Thinking; Graphic Design; Reconstruction